STUDY ON LOW SPEED IMPACT PERFORMANCE OF FIBER-METAL LAMINATES - MA YaoHui; CUI An; LIU FangFang; JIN WeiGuang; XU YingPing (Jixie qiangdu)
Two kinds of aluminum alloy sheets, AL5052 and AL6061, and basalt fiber cloth are selected to be laid as symmetrical and alternate layers to manufacture fiber-metal laminates with different structures. The bending and low-speed impact performance of the laminate structure are tested and compared; the laminate low-speed impact simulation model is established to study the influence of laminates fiber layup methods on the low-speed impact resistance; the thickness of aluminum alloy plates were optimized with multiple objectives to obtain the best thickness values of each layer of aluminum alloy plates; the optimal laminate structure is applied to the external panel of a car door for column collision simulation analysis. The results show: compared with the original door, the energy absorption characteristics and weight reduction effect of the fiber metal laminate door have been improved obviously.